Praca emocjonalna nauczyciela w koncepcji kulturowej Arlie Hochschild – (nowy) wymiar sukcesu pedagogicznego nauczyciela - Przybylska, Irena (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
This paper attempts to interpret teacher’s work from the perspective of their emotional „inputs”. Referring, inter alia, to the concept of Arlie Hochschild, the author highlights three dimensions of emotional work: building emotional climate in the classroom, forming emotional competence and reflective work on their own experiences. Theoretically the argumentationis set in three discourses: emotional work, emotions (interactive concept), and teachers (the ontology of the profession). The article ends with indication for the practice of teachers’ professional preparation which must refer not only to intellectual, communicational but also emotional ontology of profession. As teachers’ work is presented as emotional work, the implications for job selection and preparation are vivid. Strengthening emotional competences, emotional reflectivity and creativity along with academic preparation is perceived as the potential sources of success in interpersonal and intrapersonal dimensions.
Keywords: Arlie Hochschild; emocje; kultura emocjonalna; praca emocjonalna; postkonwencja